Study of the formation of porous hydroxyapatite ceramics from corals via hydrothermal process - Hien, Vu Duy; Huong, Dao Quoc; Bich, Phan Thi Ngoc (Vietnam Journal of Chemistry, 2012)
The hydrothermal method was used for preparation porous hydroxyapatite (HA) ceramic from coral scaffold, in two ways: synthesized directly from coral skeleton and synthesized from CaO, which was product of coral thermal decomposition. The obtained samples were characterized by techniques including X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The analytical results confirmed that HA ceramic was formed by the indirect synthesis from fresh obtained CaO from coral aragonite. Determined reaction conditions were at 180oC and 14 atm pressure for 36 hours.